Avaliação da toxicidade da vinhaça utilizando Oreochromis niloticus (Perciformes: Cichlidae) como organismo teste - Correia, Jorge Evangelista [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Contamination of rivers and lakes, waste disposed by infiltration into the soil as fertilizer, for example, has been highlighted around the world, since such compounds can contain toxic elements, causing changes in aquatic and/or terrestrial ecosystem. Due to the possible presence of these elements in these wastes, it is possible assess damage to organisms exposed through breaks in genetic material and mutations. In this sense, this work aimed at exploring the cytotoxic, mutagenic and genotoxic vinasse pontential, residue used as fertilizer, from the processing of sugar cane into alcohol, using fish (Oreochromis niloticus - Cichlidae) as a test organism. The individuals were exposed to different dilutions of vinasse in the water and later carried out analysis of their erythrocytes using the micronucleus test and nuclear abnormalities associated and the comet assay. In the first bioassay, tilapia exhibited 5% and 10% vinasse concentrations died after 48h. The number of micronucleated erythrocytes was statistically significant for the 1% vinasse concentration and also for nuclear abnormalities such as broken-egg and nuclear bud, when compared with negative and positive controls; were also significant lobed type erythrocytes, when compared to the negative control. The test results of the comet assay were not significant for 1% vinasse when compared to the negative control, due to the high rate of comets with damage control, which is unusual. The same was observed for changes as notched and blebbed type. In the second chemical analyzes conducted, the detection of heavy metals in the vinasse sample, charged only the presence of copper and chromium, the latter with a concentration 89 times higher than in the first test. Differentially the first bioassay, fish exposed to dilution of 5% did not die... (Complete abstract click electronic access below)

A contaminação de lagos e rios, por infiltração de resíduos dispostos no solo como fertilizantes, por exemplo, tem merecido destaque em todo o mundo, uma vez que tais compostos podem conter elementos tóxicos, causando alterações nos ecossistemas aquáticos e/ou terrestres. Dada a possível presença desses elementos nesses resíduos, é possível avaliarmos danos causados aos organismos expostos, por meio de mutações e quebras no material genético. Neste sentido, o trabalho apresentado teve como objetivo geral analisar o potencial citotóxico, genotóxico e mutagênico da vinhaça, resíduo da transformação da cana-de-açúcar em álcool, usada como fertilizante, utilizando peixes (Oreochromis niloticus - Cichlidae) como organismo teste. Os indivíduos foram expostos a diferentes diluições de vinhaça na água e, posteriormente, foi realizada a análise dos seus eritrócitos utilizando o teste do micronúcleo associado às anormalidades nucleares e o ensaio do cometa. No primeiro bioensaio, as tilápias expostas as concentrações de vinhaça de 5% e 10% morreram após 48h. O número de eritrócitos micronucleados foi estatisticamente significativo para a vinhaça na concentração 1%, e também para as anormalidades nucleares broken-egg e broto, quando comparado aos controles negativo e positivo; foram significativos também os eritrócitos tipo lobed, quando comparado ao controle negativo. Os resultados obtidos no ensaio do cometa não foram significativos para a vinhaça 1% quando comparados ao controle negativo, devido ao alto índice de cometas com danos no controle, o que não é usual. O mesmo foi observado para as alterações do tipo “notched” e “blebbed”. No segundo bioensaio as análises químicas realizadas para a detecção de metais pesados na amostra de vinhaça, acusaram apenas a presença de cobre e cromo, esse último... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Água - Poluição; Citotoxicidade; Toxicologia genética; Toxicidade - Testes; Ecologia aquatica; Mutagenese; Tilapia (Peixe); Vinhaça